Synoptics of Things (SoT): an open framework for the supervision of IoT devices - Serras, Bruno (2021)
In the industry, there is a need to manage and monitor systems and their associated devices. This process can be quite complex when the technological landscape is composed of several heterogeneous systems. In such scenarios, both the systems and their devices can be from different suppliers, each one with its own interfaces, often proprietary and non standardized. Moreover, several different administrators can be responsible for the supervision of a system, which greatly complicates the process of supervising multiple systems. Yet, overviewing a technological landscape can be facilitated by the concept of Synoptics, as a fundamental part of a supervisory control and data acquisition system. As modern applications become more and more web based, it makes sense to use web browsers to implement the concept of Synoptics. In this paper, we present the Synoptics of Things (SoT) framework to extend the Synoptics concept to the web domain. The proposed SoT framework explores the concept of Web Components as a standard to enable the development of custom and reusable components for modern web browsers. Such components, or Widgets-IoT, as we call them, can function as an abstraction of both IoT devices and informatics systems, facilitating the interaction with the supervising operators. Accordingly, we present and discuss the use of the SoT framework in an Informatics System of Systems reference implementation to monitor and control the involved systems and the various executive services that compose them.